Transformative Service and Public Satisfaction: Insights from Indonesia's Public Service Malls - Permata Sari, Indah; Lanin, Dasman; Saputra, Boni; Gomes da cruz Fernandes, Benjamin (Universitas Medan Area, 2025)
This study examines the influence of transformative service dimensions on public satisfaction at the Public Service Mall (PSM) in Payakumbuh City, Indonesia. While PSMs have emerged as integrated service innovations, a significant gap remains in understanding how specific transformative service dimensions affect public satisfaction in developing countries. Employing an associative quantitative approach, this research collected data from 220 service users through structured questionnaires and analyzed it using multiple regression. The findings reveal that individual well-being dimensions contributed the highest impact (57.2%), followed by group well-being (51.2%) and social well-being (38.9%). Simultaneously, these three dimensions explained 88.7% of the variance in public satisfaction (F = 1704.067, p < 0.05). These findings make theoretical contributions by extending the Transformative Service Research (TSR) framework to public administration contexts in developing countries and by identifying a hierarchy of service dimensions that shape public satisfaction. From a practical perspective, this research provides policymakers with empirical evidence on the importance of balancing individual and collective well-being interventions in the development of PSM. This study addresses a literature gap by providing the first empirical evidence on TSR application in integrated public service facilities within a non-Western developing country context, specifically Indonesia.